2017
DOI: 10.3389/fmicb.2017.00120
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Consequences In vivo and In vitro of Rearranging the P Gene of RABV HEP-Flury

Abstract: Phosphoprotein (P) of the Rabies virus (RABV) is critically required for viral replication and pathogenicity. Here we manipulated infectious cDNA clones of the RABV HEP-Flury to translocate the P gene from its wild-type position 2 to 1, 3, or 4 in gene order, using an approach which left the viral nucleotide sequence unaltered. The recovered viruses were evaluated for the levels of gene expression, growth kinetics in cell culture, lethality in suckling mice and protection of mice. The results showed that viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…Our results demonstrated that rHEP-SH-P showed significant lower pathogenicity in mice compared to GD-SH-01, which was consistent with previous studies that show that G protein mainly contributes to the pathogenicity of RABV, rather than P protein (Dietzschold et al, 1983;Ito et al, 2001;Pulmanausahakul et al, 2008), whereas the P gene facilitated viral pathogenesis, as previously reported that P gene-deficient RABV strain was apathogenic to host (Morimoto et al, 2005). Our previous study demonstrated that the lower expression of P gene resulted in weaker pathogenic outcomes (Mei et al, 2017). In the present study, despite that the G gene expression of HEP-Flury and rHEP-SH-P was not significantly different, rHEP-SH-P bearing suppressed P gene was less pathogenic than HEP-Flury.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results demonstrated that rHEP-SH-P showed significant lower pathogenicity in mice compared to GD-SH-01, which was consistent with previous studies that show that G protein mainly contributes to the pathogenicity of RABV, rather than P protein (Dietzschold et al, 1983;Ito et al, 2001;Pulmanausahakul et al, 2008), whereas the P gene facilitated viral pathogenesis, as previously reported that P gene-deficient RABV strain was apathogenic to host (Morimoto et al, 2005). Our previous study demonstrated that the lower expression of P gene resulted in weaker pathogenic outcomes (Mei et al, 2017). In the present study, despite that the G gene expression of HEP-Flury and rHEP-SH-P was not significantly different, rHEP-SH-P bearing suppressed P gene was less pathogenic than HEP-Flury.…”
Section: Discussionsupporting
confidence: 92%
“…The RNP is a key role in the viral assembly and replication; RABV P protein serves as a component of RNP affecting viral replication indirectly. Actually, the formation of RNP was influenced by the optimal ratio of N:P:L (Pattnaik and Wertz, 1990;Mei et al, 2017), which was reflected by the suppressed N and L expression in the current study and suggested that the low level of P gene expression limited the viral replication by obstructing the formation of RNP. A previous study suggested the poor proliferative capacity of rHEP-SH-P in vitro (Tian et al, 2017b); in the current study, we observed relatively lower viral growth of rHEP-SH-P in vivo, which was due to the suppressed P gene.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…All virus stocks were prepared in NA cells and stored at -80°C. Viruses were titrated in NA cells using fluorescein isothiocyanate-conjugated antibodies directed against N of RABV (FujiRebio Diagnostic Inc., PA, United States), as described previously ( Mei et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Virus spread assay was conducted using NA cells on 6-well plate as described previously [19,20]. Briefly, NA cells were infected with RABV at an MOI of 0.01, and incubated for 2 h at 37 • C. The inoculum was removed and cells were washed with PBS.…”
Section: Assessment Of Virus Spreadmentioning
confidence: 99%